Model â€œThe Best Proccesâ€ Pendidikan Bermutu dan Berdaya Saing - Suwarjono Suwarjono (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2017)
The rationale of this article is based on the quality of the school and the quality of the graduates is still low, the implementation of sentaralistic education, the school management is not appropriate, the input-output analisys approach, the community participation is still weak, and cooperation is still low. Then the required management model that can create a quality education and competitive. Model "The Best Procces" quality education and competitiveness can be one solution in creating quality education and competitive. This model aims to create high quality schools and graduates, namely schools that prioritize good planning, implementation, and evaluation processes, supported by management that has the character of improving students' cognitive, affective, psychomotoric, believing skills, and operational skills, leadership skills skills.